The Correlation between the History of Antenatal Care Visits during The Covid -19 Pandemic and Stunting Incidents - Ratih Mega Septiasari; Dian Mayasari; Yesika Nadya (STIKes Patria Husada Blitar, 2023)
Stunting occurs due to chronic malnutrition that has been going on for a long time, namely from the time the child is in the womb until the child is 2 years old. Limited access to antenatal care is one of the causes of stunting. The COVID-19 pandemic has had an impact on health services, including maternal and child health services. The purpose of this study was to analyze the correlation between the history of antenatal care visits during the COVID-19 pandemic and the incidence of stunting. This was a quantitative study using an observational case-control research design with a retrospective approach. The population was all mothers who had babies aged 0â€“12 months in Kebonagung Village area, Pakisaji District, Malang Regency. The sampling technique used total sampling. The sample was 70 respondents. The data obtained were analyzed using the Chi-squared correlation test with a p value of 0.05. The results showed that there was a significant correlation between antenatal care visits during the COVID-19 pandemic and the incidence of stunting in the Kebonagung Village area, Pakisaji District, Malang Regency, with a p value of = 0.000 (pÂ < 0.05). with moderate closeness and a correlation coefficient value of (r) = 0.2352. It is expected that health workers will provide counseling, information, and education to pregnant women about the importance of prenatal checks to prevent stunting